Preventing severe influenza in Australian infants: Maternal influenza vaccine effectiveness in the PAEDS-FluCAN networks using the test-negative design. Issue 19 (26th April 2022) - McRae, J.; Blyth, C.C.; Cheng, A.C.; Quinn, H.E.; Wood, N.; Macartney, K.K.; ,
Highlights: First multi-state study from Australia on maternal vaccine effectiveness against severe infant influenza. Influenza vaccination in pregnancy provides greatest protection for infants aged < 2 months. Despite free availability of the influenza vaccine, uptake in pregnant women remains low.